Inflection and derivation in verbal morphology: a borderline case from agglutinative languages. - Nkollo, Mikołaj (Studia Romanica Posnaniensia, 2004)
The present paper focuses on the linguistic status of causative formatives in Kazakh verbal morphology. In Kazakh traditional grammars, these morphological elements are claimed to represent factitive voice. Hence, they are viewed as an instance of inflection. This point of view is subject to thorough investigation. It is argued that word's single occurrence cannot cumulate several values of one grammatical category (e.g. nouns are never doubly marked for the category of number, adjectives are never carriers of more than one value within the category of degree, etc.). Kazakh verbs, in their turn, are able to contain the factitive and passive (or reflexive) morpheme at a time. The reason of this compatibility lies in merely derivational (non-categorial) nature of causative modifiers in verbal morphology of Kazakh language.